MENGHADAPI DEGRADASI ETIKA DAN MORAL SEBAGAI PROBLEMATIKA GENERASI MILENIAL DENGAN PERSPEKTIF PENDIDIKAN AGAMA HINDU - I Dewa Gede Darma Permana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Ethics and morals are teachings that teach humans to use their strengths in the form of mind and intelligence in order to be able to know the limits of good and bad values in an act. Everyone is obliged to have these ethical and moral values as a guide in thinking, speaking and acting, including the Millennial generation. Millennial generation is a special generation, because it is the next generation of young people and bearers of the future direction of the nation. Facing these roles and responsibilities is not something easy for Millennials today also need to face various problems Millennials, one of which is the degradation of ethics and morals. For this reason, in this paper, ethical and moral degradation as a problem of the Millennial generation today is discussed and explored more deeply using the perspective of Hindu Religious Education. Later in writing using this type of qualitative research with the method of collecting literature studies and interactive data analysis techniques by Miles and Huberman, which in analyzing qualitative data consists of three activity streams, namely reducing the data or sorting the data that has been collected, presenting the sorted data, and finally drawing a conclusion or verifying the data that has been analyzed. From the results of this study, it is found that the factors that cause these problems, including poor family resilience, bad social environment, and finally the unwise use of technology from the Millennial generation itself.